Burundi: analysis of the 2016-2017 Burundian demographic and health survey - Prosper, Masabarakiza; Charles, Nsanzabera (International Journal Of Community Medicine And Public Health, 2021)
Background: Access to antenatal care and postnatal care services has a great deal of impacts on major causes of high maternal, neonatal and child mortality rates. This study was aimed to identify factors affecting the use of antenatal care (ANC) and postnatal care (PNC) services. Methods: The study used data from the nationally representative 2016-2017 Burundi demographic and health survey (DHS). A total of 8,660 mothers who gave birth within five years preceding the 2016-2017 Burundi DHS were included in this study. Logistic regression statistical analyses were used to identify factors associated with the use of the first ANC visit, the use of 4 ANC services and the use of PNC services in Burundi. Results: Using logistic regression the determined factors such as birth order (AOR 1.64; 95% CI 1.51-1.73), place of delivery (AOR 0.63; 95% CI 0.54-0.76), mothers’ education (AOR 0.47; 95% CI 0.38-0.57) and husband’s education level (AOR 0.85; 95% CI 0.74-0.94) were associated with the use of early ANC. Factors such as birth order (AOR 1.79; 95% CI 1.67-2.30), the exposure to media(AOR 1.11; 95% CI 0.98-1.30), women’s education (AOR 0.58; 95% CI 0.46-0.73), residence(AOR 0.8; 95% CI 0.69-1.01) and the birth interval(AOR 1.45; 95% 1.32-2.00) were associated with the four ANC. Women’s education (AOR 0.59; 95% CI 0.40-0.70), and health insurance coverage (AOR 0.72; 95% CI 0.59-0.96) were associated with the receiving of PNC. Conclusions: Health promotion targeting women’s education, husbands’ education and behavioural change communication in rural areas are vital for increasing their awareness about the importance of antenatal services.